2013
DOI: 10.1002/jcb.24484
|View full text |Cite
|
Sign up to set email alerts
|

Growth differentiation factor‐15 (GDF‐15) suppresses in vitro angiogenesis through a novel interaction with connective tissue growth factor (CCN2)

Abstract: Growth differentiation factor-15 (GDF-15) and the CCN family member, connective tissue growth factor (CCN2), are associated with cardiac disease, inflammation, and cancer. The precise role and signaling mechanism for these factors in normal and diseased tissues remains elusive. Here we demonstrate an interaction between GDF-15 and CCN2 using yeast two-hybrid assays and have mapped the domain of interaction to the von Willebrand factor type C domain of CCN2. Biochemical pull down assays using secreted GDF-15 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 77 publications
0
25
0
Order By: Relevance
“…GDF15 has been found to have pro- or anti-angiogenic effects based on the cellular microenvironment/stressor (Song et al, 2012; Whitson et al, 2013). HUVECs exposed to hyperoxia showed a robust induction in GDF15 mRNA and protein levels and this was higher in male cells.…”
Section: Discussionmentioning
confidence: 99%
“…GDF15 has been found to have pro- or anti-angiogenic effects based on the cellular microenvironment/stressor (Song et al, 2012; Whitson et al, 2013). HUVECs exposed to hyperoxia showed a robust induction in GDF15 mRNA and protein levels and this was higher in male cells.…”
Section: Discussionmentioning
confidence: 99%
“…Because p53 is a well known angiogenesis inhibitor (Teodoro et al, 2007), it is possible that MEG3 inhibits angiogenesis via activation of p53. Whitson et al (2013) recently demonstrated that GDF15, a MEG3 activated p53 target gene (Zhou et al, 2007), suppresses angiogenesis (Whitson et al, 2013). MEG3 plays an important role in suppression of human NFAs, likely through activation of p53.…”
Section: The P53 Connectionmentioning
confidence: 99%
“…In TRAMP (transgenic adenocarcinoma of the mouse prostate) mouse prostate cancer models, GDF-15 has been demonstrated to slow cancer development but increase metastases 49. Nevertheless, GDF-15 has been recently shown to suppress in-vitro angiogenesis through its interaction with connective tissue growth factor 13,50. It is involved in apoptotic pathways and is thought to play a role in antitumor activity of tasquinimod 13.…”
Section: Other Mechanisms Of Action Of Tasquinimodmentioning
confidence: 99%